Pengembangan E-Modul Berbasis Flip PDF Professional Pada Tema 8 Subtema 2 Pembelajaran 1 - Sarah Rahayu; Dadang Kurnia; Yuli Mulyawati (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This study aims to determine the development and feasibility of a flip pdf professional based e-module to be developed for Class IV students at SDN Genteng Bogor City regarding the learning process carried out at school. The method used in this study is using the Research and Development model, but in this study it reaches the development stage because it is only to find out the development of flip pdf professional based e-module teaching materials. In this study, a validation test was carried out on experts. These experts are media experts, linguists and material experts to develop and refine professional flip pdf based e-modules, and distribute student questionnaires to determine the feasibility of professional flip pdf based e-modules in learning. The results of the validation test by media experts with a percentage of 89% with very feasible criteria, linguists with a percentage of 80% with appropriate criteria and material experts with a percentage of 88% with very feasible criteria. And the results of the student response questionnaire also showed results with a percentage of 93.33% in the very good category, so these results show that e-modules are very feasible to be developed and used as teaching materials in the learning process.Â